Chicken Oil as The New Cooking Oil : Its Effect on Lipid Profile and Liver Histology in Male Wistar Rats - Andi Asda Astiah; Syahrijuita Syahrijuita; Ika Yustisia (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACTBackground: The selection of the appropriate cooking oil by society will reduce high fat intake. Chicken oil as a new cooking oil that is starting to be used by some people as a substitute for palm oil, needs to be studied for its health effects.Objectives: This study aimed to see and compare changes in lipid profiles and liver histology in male Wistar rats fed with chicken oil and palm oil.Methods: Male Wistar rats (n = 10) were separated into two groups randomly, namely the chicken oil group and the palm oil group. Each rat in the group was given oil at a dose of 1 mL/day. Before treatment, lipid profile levels were measured, and after four weeks of treatment, lipid profile levels and liver histology were examined.Results: Administration of 1 mL/day of oil in each group for four weeks diminished total cholesterol, HDL, LDL levels at the two groups also increased triglyceride levels in the two groups, but non-significant differences among groups. This research also showed the formation of hepatic steatosis in all groups, but still mild-moderate microvesicular steatosis, and non-significant differences among groups.Conclusion: The consumption of 1 mL/day of chicken oil for four weeks has a similar effect on lipid profiles and liver histology as the consumption of 1 mL/day of palm oil with the same duration. We propose further study by administering the intervention of chicken oil to rats for a longer time.